Using plastic bags and its damaging impact on environment and agriculture: an alternative proposal - Jalil, Md. Abdul; Mian, Md. Nannu; Rahman, Muhammad Khalilur (Macrothink Institute, 2013)
Thousands of plastic factories are producing tons of plastic bags which are very popularly used by the people for shopping purposes because of its ease, cheapness and convenience of use but their very hazardous negative impact is never highlighted or, at the very least, openly discussed in a more serious tone. Many countries have banned plastic bags due to public concern over the serious negative impact on the environment and agriculture, especially, in agricultural countries, such as Bangladesh, India, Pakistan, South Africa, etc. In this research paper, qualitative research methodology has been used to analyze our ideas based on literature review and interview from experts. The paper focuses on the sustainable agricultural and economic development by finding out alternatives to the use of ever harmful plastic bags. Key words: Plastic bags, environmental degradation, impact